The political economy of terrorism - Enders, Walter, 1948-; Sandler, Todd.; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2012)
c
Includes bibliographical references and indexes.
Electronic reproduction.
Keywords: Terrorism; Terrorism -- Economic aspects; Electronic books